The origin of the pecheneg’s ethnic name - K. A. Kotkoff (Nomadic Civilization: Historical Research, 2024)
This article is dedicated to the origin of the pecheneg’s ethnic name. The latters are considered to be a turkic tribe, lived in the southern Russian and in the lower Danubian steppes in the X–XI cc. According to some authors, the gagauz people, i.e. the Turkic speaking ethnic group, living in the southern part of Moldova, in Budjak and in Dobruja, are descendants of the pechenegs, but it has no real proofs. There are different but unconvincing versions about the origin of the pecheneg’s ethnic name. This ethnonim has no any traces of Turkic ethymology, so it cannot be of any Turkic origin. Highly likely, the pecheneg’s ethnic name came from the russian word “pochinók” (i.e. a colony). It is confirmed by another name of a part of the pechenegs — the kangars. The latter came from the Turkic word “khongorai”, which has the same meaning as the Russian word “pochinok”. The medieval narratives describe pechenegs as different cossack-like communes, mostly of the Russian origin, partially of the Turkic origin, lived in the southern Russian and Ukrainian steppes in the Middle Ages.